Developing strategies to improve the technical and vocational education training system in Swaziland - Mdluli, Grace Sizakele (My University, 2015)
The purpose of this study was to develop strategies to improve Technical and Vocational Education and Training (TVET) in Swaziland. It has been 68 years since the TVET education was introduced in the country, but it has slowly been coming forth, especially in providing for the needs of society and industry. For this reason, the researcher wanted to find out what could be delaying the progress of the TVET system by developing some strategies to improve this aspect of training. The fundamental research questions were based on the strategies that could be developed to improve the TVET system in Swaziland and the importance of ensuring pre-service and in-service training for special target groups. It was worth mentioning that since the TVET policy had been officially launched and implemented, different stakeholders who would be expected to fully support and understand what the policy entails would recognise its functions. The policy states that skills training should be introduced in the school system at the earlier years of starting the school system to create awareness and love for various skills at an early age. In addition, it is imperative that the country give priority to the TVET versus the academic education as it had been proved through the unemployment rate that the jobs are actually shrinking whilst the work in the market is in abundance. Hence, there was a need to strategise methods of successfully implementing the TVET policy in order to benefit the government’s efforts in the aims and objectives set in the policy The study aimed at examining the challenges faced by the country in implementing the policy so that it could effectively address the TVET education in the most positive and successful manner. The main findings form part of the important basis of the study by providing evidence of research phenomenon that it is anticipated to denote. The findings of the study were discussed according to the participants’ responses collected during focus group interviews and individual in-depth interviews. Further developments for TVET improvement of the study showed the findings portray that there is a need to improve resource efficiency strategy and the private sector/industry should provide support to TVET students, via internships, attachment of identified relevant training staff, sharing of equipment or the provision of training programmes.
D. Tech. (Business, Faculty of Management Sciences) Vaal University of Technology
Keywords: Vocational education; Technical education; TVET system in Swaziland; In-service training; Skills training; Internships; 370.113096887; Industry and education; Education -- Swaziland.